Deep forgery discriminator via image degradation analysis. Issue 11 (7th May 2021) - Yu, Miaomiao; Zhang, Jun; Li, Shuohao; Lei, Jun; Wang, Fenglei; Zhou, Hao
Abstract: Generative adversarial network‐based deep generative model is widely applied in creating hyper‐realistic face‐swapping images and videos. However, its malicious use has posed a great threat to online contents, thus making detecting the authenticity of images and videos a tricky task. Most of the existing detection methods are only suitable for one type of forgery and only work for low‐quality tampered images, restricting their applications. This paper concerns the construction of a novel discriminator with better comprehensive capabilities. Through analysis of the visual characteristics of manipulated images from the perspective of image quality, it is revealed that the synthesized face does have different degrees of quality degradation compared to the source content. Therefore, several kinds of image quality‐related handicraft features are extracted, including texture, sharpness, frequency domain features, and deep features, to unveil the inconsistent information and modification traces in the fake faces. In this way, a 1065‐dimensional vector of each image is obtained through multi‐feature fusion, and it is then fed into RF to train a targeted binary classification detector. Extensive experiments have shown that the proposed scheme is superior to the previous methods in recognition accuracy on multiple manipulation databases including the Celeb‐DF database with better visual quality.